Pituitary adenoma: literature review and association with TAS2R16 (rs978739, rs1357949) gene polymorphisms - E. Pileckaitė; G. Gedvilaitė; L. Kriaučiūnienė (Neurologijos seminarai)
The pituitary gland is the primary regulatory gland in the endocrine system transmitting signals from the hypothalamus to target organs through hormone release. Through the release of hormones, the pituitary gland regulates vital physiological functions: growth, reproduction, metabolism, and the stress response. Disorders in the pituitary gland can cause damage, such as pituitary adenomas (PA). PA is the most common benign tumor arising from epithelial cells of the anterior pituitary gland. PA is one of the most common tumors of the central nervous system. PA is differentiated by hormone secretion into non-secretory (non- functional) and secretory (functionally active). Excess hormones secreted by PA can cause clinical syndromes, such as hyperprolactinemia (caused by excessive secretion of prolactin), acromegaly (due to excess growth hormone), and Cushing’s syndrome (due to excessive production of the adrenocorticotropic hormone ACTH)). Studies show that the prevalence of adenomas in the population is approximately 80/100,000. The occurrence of PA is influenced not only by somatic or germ cell defects but also by environmental factors. The exact cause of PA is still unclear, but it is known that a small part (~5%) of PA due to hereditary syndromes is caused by gene changes. Considering the influence of environmental factors and genetic alterations that affect the occurrence of PA, new genetic markers can be searched to detect this disease. One of the risk factors contributing to the development of PA and its aggressiveness is alcohol consumption. Excessive alcohol consumption affects not only the development of PA but also the manifestation of other cancers. A recent study has investigated the association of TAS2R16 gene single nucleotide polymorphisms (SNPs) with colon cancer, as SNPs in this gene have been found to increase alcohol dependence. Based on the association of TAS2R16 SNPs with cancer, we decided to investigate the association of TAS2R16 gene (rs978739, rs1357949) polymorphisms with PA.